‘This is Africa’: Filmic Negotiations of Crime, Justice and Global Responsibility - Duncanson, Kirsty (2011)
Film is a significant medium through which Western audiences learn about crime and suffering occurring beyond their national borders. On this basis, this article critically reflects on the ‘knowledge’ of criminal violence in contemporary Africa provided by two recent films, Blood Diamond (2006) and Sometimes in April (2005). We argue that the films offer notably divergent understandings of the nature of violent conflict in post-colonial Africa, and of who is capable of bearing the responsibility to address its causes and legacy. While Blood Diamond adopts a conventional colonial narrative in which Africa, through the example of Sierra Leone, is portrayed as a place of disorder ultimately requiring the intervention of the West, Sometimes in April offers an alternative image of a more autonomous African nation, able to actively negotiate the challenges of the post-conflict and post-colonial environment.Sydney Institute of Criminology; School of Social Sciences at the University of Western Sydne